Exploring the impact of Crohn's disease on the intragastric environment of fasted adults - Maria Vertzoni; Christina Koulouri; Androniki Poulou; Konstantinos Goumas; Christos Reppas (International Association of Physical Chemists (IAPC), 2020)
We explored the potential impact of Crohn's disease on the intragastric environment of fasted adults with a view to potential effects on intragastric performance of orally administered drugs in the fasted state. Data were collected from 15 healthy individuals and 15 patients with Crohn's disease. All subjects remained fasted for at least 12h prior to gastroscopy. Intragastric resting volume and pH were measured upon aspiration. Osmolality, surface tension, pepsin activity, and content of six bile acids were measured within 4 months upon sample collection. Unlike intragastric volumes, intragastric osmolality was significantly increased by Crohn's disease. However, mean osmolality value in patients was only slightly higher than in healthy individuals (293 vs. 257 mOsmol/kg, respectively), therefore, unlikely to affect intragastric drug product performance. Primarily due to the high variability of data in healthy individuals, the potential effects on intragastric pH and surface activity could not be evaluated on a statistical basis. However, based on average (mean and median) values, even if they are statistically significant, it seems unlikely to be of clinical significance. Inter-subject variability of pepsin activity, and total bile acids content was high in both the healthy and the patients' groups. Statistical investigation of the potential impact of Crohn's disease on these parameters requires prior designation of the minimum differences to be detected; such differences will determine the minimum sample size required of relevant investigations.